La Cooperación Necesaria y la Complicidad en la Ultima Reforma y Adicion al Codigo Penal del 2002 (Revista de Derecho, 2012)
DOI: http://dx.doi.org/10.5377/derecho.v0i3.718 Revista de Derecho No.3 2002 pp.89-131